Social amoebae: environmental factors influencing their distribution and diversity across south-western Europe. - Romeralo, María; Moya-Laraño, Jordi; Lado, Carlos (Microbial ecology, 2011)
The social amoebae (dictyostelids) are the only truly multicellular lineage within the superkingdom Amoebozoa, the sister group to Ophistokonts (Metazoa+Fungi). Despite the exceptional phylogenetic and evolutionary value of this taxon, the environmental factors that determine their distribution and diversity are largely unknown. We have applied statistical modeling to a set of data obtained from an extensive and detailed survey in the south-western of Europe (The Iberian Peninsula including Spain and Portugal) in order to estimate some of the main environmental factors influencing the distribution and diversity of dictyostelid in temperate climates. It is the first time that this methodology is applied to the study of this unique group of soil microorganisms. Our results show that a combination of climatic (temperature, water availability), physical (pH) and vegetation (species richness) factors favor dictyostelid species richness. In the Iberian Peninsula, dictyostelid diversity is highest in colder and wet environments, indicating that this group has likely diversified in relatively cold places with high levels of water availability.
Keywords: Biodiversity; Biological; Dictyosteliida; Dictyosteliida: classification; Dictyosteliida: genetics; Dictyosteliida: isolation & purification; Dictyosteliida: physiology; Ecosystem; Models; Portugal; Soil; Soil: parasitology; SPAIN (citation)

RESPONSE OF MEDITERRANEAN GRASSLAND SPECIES TO CHANGING RAINFALL. - Figueroa, M. E.; Davy, A. J. (Journal of Ecology, 1991)
Investigates the long-term changes in the composition of a species-rich Mediterranean grassland in south-western Spain. Determination of the frequency of every species of herbaceous vascular plants annually; Domination of winter annual vegetation; Correlations between the logit of the total annual frequency of each species and rainfall totals; Link between species abundance and rainfall.
Keywords: BOTANY; Grasslands; MEDITERRANEAN Coast (Spain); RAINFALL frequencies; SPAIN (citation)

RESPONSE OF MEDITERRANEAN GRASSLAND SPECIES TO CHANGING RAINFALL. - Figueroa, M E; Davy, A J (Journal of Ecology, 1991)
Investigates the long-term changes in the composition of a species-rich Mediterranean grassland in south-western Spain. Determination of the frequency of every species of herbaceous vascular plants annually; Domination of winter annual vegetation; Correlations between the logit of the total annual frequency of each species and rainfall totals; Link between species abundance and rainfall.
Keywords: BOTANY; Grasslands; MEDITERRANEAN Coast (Spain); RAINFALL frequencies; SPAIN (citation)